Wear Prediction of Curved Switch Rail in High-Speed Turnout and Influence of Wheel and Rail Wear on Vehicle Dynamic Performance - Shuo Yan; Taotao Jin; He Ma; Jun Zhang; Yi Zhou (Applied Sciences, 2023)
A wear prediction model is built to research the wear of the curved switch rail in a high-speed turnout. The Archard wear model is used in the wear prediction model to analyze the profile evolution law. The non-Hertzian contact Kik–Piotrowski method based on virtual penetration is used as the contact algorithm for the Archard wear model. A dynamic model of the vehicle–curved switch rail system based on the predicted profiles of the curved switch rail and the measured wheel profiles with different stages is established. The effect of the wheel and curved switch rail profiles’ wear on vehicle dynamic performance is analyzed. The results show that the wheel completely transitions from the stock rail to the curved switch rail between 35 and 50 mm head widths. As the head width of the curved switch rail increased, the position of the maximum wear depth gradually moved to the gauge shoulder. When the total passing weight of the train is 50 Mt, the 20 mm head width curved switch rail side wear reaches a maximum of 5.3 mm. The position in which the wheel transitions from the stock rail to the curved switch rail will be further away from the tip of the curved switch rail due to wheel–rail wear. Regarding the derailment coefficient, the wheel–rail vertical force and lateral force are both significantly impacted. However, they have little effect on the vertical and lateral acceleration of the vehicle. The wear of the wheels and rails has a higher impact on vehicle driving safety and a lower impact on vehicle driving stability.